Integrated solid wastes management for KL - Kabbashi, Nassereldeen Ahmed; Jami, Mohammed Saedi; Mirghani, Mohamed Elwathig Saeed (2010)
Issues on pollution and waste disposal problems have post a great challenge to manager and planner of Kuala Lumpur since the number of population and the growth of industry sector in Malaysia have been increased. The purpose of this research is to study the current solid waste management in Kuala Lumpur and to recommend as well as develop an integrated approach by using knowledge-based system. Data on solid waste disposal system and waste generated by various regions in Kuala Lumpur from Department of Environment (DOE) Malaysia, Dewan Bandaraya Kuala Lumpur (DBKL), and Alam Flora Sdn Bhd (AFSB) are collected in order to be implemented in the expert system. A programming language called Visual Basic is used since it is an ideal programming language for developing sophisticated professional applications for Microsoft Windows. In this project, the user interface on solid waste management is designed and the conceptual structure of the relational database model on “solid waste management system” is graphically summarized. The overall development of expert system has been carried out in several phases, including problem definition, knowledge acquisition, knowledge base, prototype development, prototype validation and implementation. Solid waste expert system contains sub forms which the user can obtain a comprehensive background of the current solid waste management in Kuala Lumpur. It allows the user to browse around the knowledge that has been extracted from books, published research articles, reports, and expertise who involved in solid waste management activities. User can ask for clarification, view the problems faced in solid waste management, forecast the future trend of solid waste generation and learn how to solve the problems in solid waste management.